PILOMATRIX CARCINOMA IN A 4-YEAR OLD CHILD WITH AN UNUSUAL PRESENTATION - Naveed, Hania; Nausheen Yaqoob,; Sadia Muhammad,; Kanwal Aftab,; Mohammad Rafie Raza, (Journal of Ayub Medical College Abbottabad, 2022)
Pilomatrix carcinoma is a rare, locally aggressive variant of pilomatrixoma with a high rate of recurrence and risk of distant metastasis. We report an unusual presentation of a pilomatrix carcinoma in a 4-year-old male child who presented with recurrent lesions on his left cheek. At the age of 1 month of life, he presented with a soft tissue swelling on his left cheek. The lesion showed a circumscribed proliferation of basaloid cells with central areas of eosinophilic ghost shadow cells and intermediate cells. Basaloid nests showed round to oval, hyperchromatic nuclei with open nuclear chromatin, prominent nucleoli and frequent mitoses but no marked nuclear pleomorphism or infiltration was identified. The lesion recurred twice at the same site. Both recurrences showed similar morphology as the primary tumor however there were extensive areas of stromal necrosis, infiltrating edges, frequent mitoses with atypical forms, and lymphovascular invasion. There was no marked nuclear pleomorphism. Morphological features favored a diagnosis of pilomatrix carcinoma. The child is still on follow-up and no recurrence has been identified to date. Pilomatric carcinoma is rarely reported in infants. Due to its rarity, aggressive histological features may be missed.